Toxoplasmic encephalitis: role of Human Leucocyte Antigens/alleles associated with rapid progression to Acquired Immunodeficiency Syndrome - Rodrigues,Maria de Lourdes (2016)
Abstract Background/aims The frequency of Human Leucocyte Antigens/alleles associated with rapid progression from Human Immunodeficiency Virus infection to Acquired Immunodeficiency Syndrome was evaluated in Brazilian patients with Acquired Immunodeficiency Syndrome with and without Toxoplasmic Encephalitis. Methods 114 patients with Acquired Immunodeficiency Syndrome (41 with Toxoplasmic Encephalitis, 43 with anti-Toxoplasma gondii antibodies, without Toxoplasmic Eencephalitis, and 30 without anti-Toxoplasma gondii antibodies circulating and without Toxoplasmic Encephalitis) were studied. Results Human Leucocyte Antigens/alleles associated with rapid progression to Acquired Immunodeficiency Syndrome, particularly HLA-B35, -DR3, and -DR1 allele group, were significantly less represented in patients with Toxoplasmic Encephalitis and Acquired Immunodeficiency Syndrome. Conclusion The presence of these Human Leucocyte Antigens/Alleles that predispose to Acquired Immunodeficiency Syndrome progression was associated with resistance to Toxoplasmic Encephalitis among Human Immunodeficiency Virus-1 carriers.